Primary squamous cell carcinoma of liver presenting as evolving liver abscess - Misra, Shivanshu; Subramanian, Aravinth; Gnanasekaran, Divya (Tropical Journal of Pathology and Microbiology, 2020)
Squamous cell carcinoma usually arises from the skin, head and neck region, cervix, and anal canal. 4-5% of carcinoma of unknown primary are found to be squamous cell carcinoma. Patients with primary squamous cell carcinoma of liver generally present with abdominal pain, jaundice, weight loss, loss of appetite, and rarely progressive dysphagia. Physical examination may reveal a palpable liver mass. A 60-year-old female patient presented with complaints of pain abdomen in the epigastrium and right upper quadrant associated with fever. There was no history of nausea, vomiting, anorexia, abdominal distension, diarrhea, or jaundice. The present case describes a case of primary squamous cell carcinoma of the liver presenting as liver abscess successfully treated by surgical resection. The post-operative period patient developed subacute intestinal obstruction for which diagnostic laparoscopy and adhesiolysis was done. Six months follow up patient is disease-free.